Selective Release of Doxorubicin from Cucurbit[8]uril Stabilized Gold Supra‐Pyramid Host at pH of Small Intestine. Issue 66 (6th October 2020) - Saini, Meenaxi; Ghosh, Souvik; Kumar, Viney; Roy, Partha; Sadhu, Kalyan K.
Abstract: Gold supra‐pyramid structures were obtained by the addition of acidic solution of cucurbit[8]uril (CB[8]) to an aqueous solution of citrate stabilized gold nanoparticles (AuNP). The reaction resulted in the precipitation of supra‐pyramid from the solution after just 1 min of shaking. Microscopic images confirmed formation of the supra‐pyramid. The stepwise structural transformation towards the supra‐pyramid was examined with variable concentrations of CB[8] to AuNP solution. Anionic counter parts of these acids (Br −, NO3 −, SO4 2− and Cl − ) controlled the size of the synthesized supra‐pyramids. These supra‐pyramid hosts showed uptake of three anticancer drugs: oral drugs etoposide, prednisolone and intravenous drug doxorubicin. Releases of drugs from these hosts were emulated at acidic stomach pH, basic small intestinal pH and in the presence of human serum albumin (HSA). The specific release of doxorubicin was confirmed at small intestinal pH 7.4. Poor release of drugs in presence of CB[8] specific guest 1‐adamantanamine confirmed the role of the supra‐pyramid as the exclusive host. The release of doxorubicin from the supra‐pyramid at pH 7.4 was confirmed by fluorescence microscopic imaging with prostate cancer DU‐145 cell line. Abstract : Pyramid scheme : Supra‐pyramid structures with variable sizes were developed by the addition of diverse acidic solution of CB[8] to citrate stabilized AuNP solution. Anion dependent loading of three drugs doxorubicin, etoposide and prednisolone within the cavity of supra‐pyramids and the selective release of doxorubicin at pH of small intestine had been achieved.